High-resolution kinetic characterization of the RIG-I-signaling pathway and the antiviral response - Burkart, Sandy; Schweinoch, Darius; Frankish, Jamie; Sparn, Carola; Wüst, Sandra; Urban, Christian; Merlo, Marta; Magalhães, Vladimir G.; Piras, Antonio; Pichlmair, Andreas; Willemsen, Joschka; Kaderali, Lars; et al. (Life science alliance, 2023)
RIG-I recognizes viral dsRNA and activates a cell-autonomous antiviral response. Upon stimulation, it triggers a signaling cascade leading to the production of type I and III IFNs. IFNs are secreted and signal to elicit the expression of IFN-stimulated genes, establishing an antiviral state of the cell. The topology of this pathway has been studied intensively, however, its exact dynamics are less understood. Here, we employed electroporation to synchronously activate RIG-I, enabling us to characterize cell-intrinsic innate immune signaling at a high temporal resolution. Employing IFNAR1/IFNLR-deficient cells, we could differentiate primary RIG-I signaling from secondary signaling downstream of the IFN receptors. Based on these data, we developed a comprehensive mathematical model capable of simulating signaling downstream of dsRNA recognition by RIG-I and the feedback and signal amplification by IFN. We further investigated the impact of viral antagonists on signaling dynamics. Our work provides a comprehensive insight into the signaling events that occur early upon virus infection and opens new avenues to study and disentangle the complexity of the host-virus interface.
Gesehen am 17.05.2024